To find a pasqueflower : a story of the tallgrass prairie - Hoch, Greg, 1971- (Bur oak book., 2022)
"Description: The tallgrass prairie once stretched from Indiana to Kansas to Minnesota. Most of this land is now growing corn and soybeans. In To Find a Pasqueflower, Greg Hoch shows us that the tallgrass prairie is the most endangered ecosystem on the continent, but it's also an ecosystem that people can play an active role in and help restore. This book is written in the same style and voice as Hoch's three previous books on bird species. He blends history, culture, and science into a unified narrative of the tallgrass prairie, with an emphasis on humans' participation in its development and destruction. Over the last century and a half, people have driven the tallgrass prairie toward extinction. However, for millennia before that, the tallgrass prairie was largely maintained and expanded by people, primarily through their use of fire. Without fire and people, the tallgrass prairie would be forest. Indeed, because the ecosystem is so young, there never was a time when people weren't playing a strong role in managing both the vegetation and wildlife. There is no such thing as a "presettlement" prairie, Hoch reminds us. Tomorrow's prairies, both restorations and native remnants, will depend on the care and nurturing of conservationists and laypeople. The audience for this book is anyone who is interested in prairies, prairie restoration, or the history of science and ecology in the context of the tallgrass prairie. Hoch's is the book you read on winter evenings to get some perspective on and historical/scientific context for plans for the upcoming growing season. It gives the reader background and philosophical principles to think about before they decide on their next land management actions. Between each chapter is a short vignette that gives a more personal account of Hoch's experiences with the prairie and prairie conservation efforts. He reminds us that people and the prairie have always been intertwined, and helps us reimagine the role humans play in the natural world"--